IMPLEMENTASI KEGIATAN MAGANG MAHASISWA DI RADIO ISWARA PALEMBANG MELALUI “PROGRAM SWARA SERU DAN SWARA SANTAI” - Dinni Febti Warivanda; Regina Ary Anandita; Sekar Triasih; Zafira Khoirina; Yenny Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Radio remains an important mass medium in delivering information, education, and entertainment to the public. Amid the rapid development of digital media, radio is required to continuously innovate in order to remain relevant and maintain audience engagement. One form of such innovation is implemented through relaxed and interactive broadcast programs, such as Swara Santai and Swara Seru on Radio iSWARA. The results of the internship activities show that to describe the implementation of student internship activities in radio broadcasting programs and their role in engaging listeners. The employed a descriptive qualitative method with a field practice approach, utilizing direct observation, informal interviews with broadcasters and production teams, and documentation of internship activities. The results indicate that students’ involvement in both on-air and off-air broadcasting activities enhances communication skills, self-confidence, teamwork, and technical understanding of radio broadcasting. In addition to providing valuable practical experience for students, the implementation of internship activities also contributes to the production of informative, educational, and entertaining broadcast content at Radio iSWARA, as well as strengthening interaction with listeners.